2022
DOI: 10.3390/biomedicines10061427
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Erythropoiesis by a Phytoestrogen Diarylheptanoid from Curcuma comosa

Abstract: Erythropoietin (Epo) is widely used for the treatment of anemia; however, non-hematopoietic effects and cancer risk limit its clinical applications. Therefore, alternative molecules to improve erythropoiesis in anemia patients are urgently needed. Here, we investigated the potential effects of a phytoestrogen diarylheptanoid (3R)-1,7-diphenyl-(4E,6E)-4,6-heptadien-3-ol, (ASPP 049) isolated from Curcuma comosa on promoting erythropoiesis. Treatment with C. comosa extract improved anemia symptoms demonstrated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…Magnetically sorted hiPSC-derived CD34 + cells were washed three times with cold PBS, lysed in protein-preservative buffers, and stepwise prepared for polyacrylamide gel electrophoresis, subsequently transferred to membranes by electroblotting as previously described [ 30 ]. Afterward, membranes were incubated with the primary antibodies: p-YAP1 (phospho-Ser127, 1:500, Abcam), YAP1 (1:1000, Abcam), p-WWTR1 (phospho-Ser89, 1:500, Invitrogen), WWTR1 (1:1000, Invitrogen), and GAPDH (1:20,000, Invitrogen), overnight at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnetically sorted hiPSC-derived CD34 + cells were washed three times with cold PBS, lysed in protein-preservative buffers, and stepwise prepared for polyacrylamide gel electrophoresis, subsequently transferred to membranes by electroblotting as previously described [ 30 ]. Afterward, membranes were incubated with the primary antibodies: p-YAP1 (phospho-Ser127, 1:500, Abcam), YAP1 (1:1000, Abcam), p-WWTR1 (phospho-Ser89, 1:500, Invitrogen), WWTR1 (1:1000, Invitrogen), and GAPDH (1:20,000, Invitrogen), overnight at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have revealed the constructive effects of ASPP 049, a diarylheptanoid isolated from Curcuma comosa [ 27 , 28 ], on an ex vivo CD34 + CD38 − CD90 + human HSC-culturing system. This compound potentially induces the cultured HSCs to have multi-lineage differentiation abilities in vitro, long-term reconstitution in vivo [ 29 ], as well as hematopoiesis improvement in an anemic mouse model [ 30 ]. However, the potential of HSC derivation from hiPSCs has not been investigated.…”
Section: Introductionmentioning
confidence: 99%